Java servlet books: A comparative review; Find out where you can get the best servlet coverage: 1 - Zukowski, John (Java world, 2000)
Lately, I've been asked frequently which Java servlet and JavaServer Pages books I would recommend. In fact, I was even asked when I was at a local bookstore recently. This month, I'll review five purely servlet books and four others that contain strong servlet content. Once you get past the basics, the book jumps into the moreuseful topics. The state management chapter covers how toidentify users and manage persistent session information acrossstateless HTTP requests with hidden form fields, URL rewriting,cookies, and the session tracking API. The security chapterprovides good coverage of authentication and using Secure Sockets Layer (SSL). The Java Database Connectivity (JDBC) chapter provides enough of a primer such that if you don't know the JDBC API, you'll be able toconnect and retrieve your information, as well as update it andmanage transactions after reading the chapter. While no JDBC 2.0 coverage is provided, you do get a decent discussion of how to pool your databaseconnections from your servlets. [James] Goodwill starts the book out differently than most books. Besides anoverview of the servlet architecture and its life cycle, you getan introduction to configuring the servlet developmentenvironments -- or at least, what is supposed to be the developmentenvironment. First, the book seems confused about what version ofthe Java Servlet Development Kit (JSDK) the book uses. While thecover clearly says version 2.1, the chapter says 2.0 is current.Second, the book doesn't say how to setup the developmentenvironment. It just says to get a JSDK and quickly moves onto configuring where to deploy servlets. Since the servletclasses are not part of the standard development environment andthe chapter is titled "Configuring the Development Environment,"I was expecting to learn how to configure my environment for servlet development.